Pengaruh Pandemi Covid-19 Terhadap Pemberian Opini Going Concern Dengan Profitabilitas Dan Leverage Sebagai Variabel Mediasi - Joshua Adiguna Prastowo; Yulius Jogi Christiawan (Business Accounting Review, 2021)
Pandemic situations causing a firm experiencing subtantial loss and threatening their sustainability business activities. Therefore, the auditor will give a going concern opinion if they doubt the firm’s sustainability because of the pandemic effects. This study aims to prove wether a firm's low-rate profitability or high-rate leverage will make the firm get a going concern opinion. The sample of this study used 40 firms that listed on Indonesia Stock Exchange for the year 2019 and 2020 on affected sectors consisting of tourism, hotels, transportation, tertiary product, property, and energy. This study used  Partial Least Square analysis. The results shows that the relationship between COVID-19 pandemic and going concern opinion decision doesn’t have a direct effect, but through profitability rate. These results are corresponding with agency theory where the owner of the company needs a third party that is the auditor to assess the company's ability through an opinion. This research contributes to the firm's concern about what causes the decline in profitability when the company gets a going concern opinion.